2013
DOI: 10.1007/978-3-642-40501-3_9
|View full text |Cite
|
Sign up to set email alerts
|

Social Information Behaviour in Bookshops: Implications for Digital Libraries

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Abstract. We discuss here our observations of the interaction of bookshop customers with the books and with each other. Contrary to our initial expectations, customers do not necessarily engage in focused, joint information search, as observed in libraries, but rather the bookshop is treated as a social space similar to a cafe. Our results extend the known repertoire of collaborative behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 20 publications
3
14
0
Order By: Relevance
“…In the library our observations lasted two to three times longer than in the bookshop. This use of the library further supports the premise of third spaces in digital libraries discussed by Cunningham et al [13].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the library our observations lasted two to three times longer than in the bookshop. This use of the library further supports the premise of third spaces in digital libraries discussed by Cunningham et al [13].…”
Section: Discussionsupporting
confidence: 81%
“…We noted previously that bookshops are predominantly social spaces / third places with the social uses of these spaces addressing more than just book search or book purchasing needs [13]. Our suggestions address how to incorporate this aspect of libraries and bookshops for families using digital libraries.…”
Section: Series and Recurring Charactersmentioning
confidence: 97%
“…They find that enquiries often arise from cultural context-reading with others, references and reviews in media-and argue that customers' mental models may deviate from the standard bibliographic metadata. Cunningham et al [8] studied collaborative information behaviour in bookshops. They found that groups of customers use many different ways to share information about books, e.g., talking aloud, pointing, reading, and searching together, and that they use these interactions to achieve agreement on which books to select.…”
Section: Related Workmentioning
confidence: 99%
“…The few prior studies of information behavior in bookshops demonstrate very little evidence of encountering (or exploration in general). But this is perhaps because of their focus -on enquiries made by customers [27], collaborative interactions with books [38], children's book selection process for recreational reading [39] and general reading practices [28]. Although one study had a think-aloud element [39], all were primarily based on anonymous observations, which limits capture of rationale for choosing books.…”
Section: Bookshops As Information Environmentsmentioning
confidence: 99%